2016
DOI: 10.4103/2008-322x.194070
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial photorefractive keratectomy for low to moderate myopia in comparison with conventional photorefractive keratectomy

Abstract: Purpose:To compare the effectiveness, safety and stability of the results of transepithelial photorefractive keratectomy (tPRK) with conventional photorefractive keratectomy (PRK) for low to moderate myopia.Methods:In this prospective non-randomized case-control study, patients with low to moderate myopia were assigned to the tPRK group (cases) or the PRK group (controls). In the tPRK group, eyes were treated using the Amaris excimer laser (SCHWIND eye-tech-solutions GmbH and Co. KG, Germany). Outcome measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 19 publications
2
45
1
Order By: Relevance
“…This approach has the advantage of not requiring the creation of a corneal flap and is less likely to induce dry eyes after treatment than LASIK. Several options to remove the epithelium exist, including photorefractive keratectomy using mechanical removal 248 , epipolis laser in situ keratomileusis using a special microkeratome 249,250 , laser-assisted subepithelial keratectomy using alcohol 251 and transepithelial photorefractive keratectomy using an excimer laser 252 . The outcomes of surface ablation are similar to those of LASIK, but the removal of the corneal epithelium can result in more patient discomfort after surgery during recovery of the corneal epithelium 248,253 .…”
Section: Surgical Treatment Of Myopiamentioning
confidence: 99%
“…This approach has the advantage of not requiring the creation of a corneal flap and is less likely to induce dry eyes after treatment than LASIK. Several options to remove the epithelium exist, including photorefractive keratectomy using mechanical removal 248 , epipolis laser in situ keratomileusis using a special microkeratome 249,250 , laser-assisted subepithelial keratectomy using alcohol 251 and transepithelial photorefractive keratectomy using an excimer laser 252 . The outcomes of surface ablation are similar to those of LASIK, but the removal of the corneal epithelium can result in more patient discomfort after surgery during recovery of the corneal epithelium 248,253 .…”
Section: Surgical Treatment Of Myopiamentioning
confidence: 99%
“…This avoided the need for alcohol epithelial debridement or mechanical removal of the epithelium during PRK [7,8]. TPRK requires only one-step removal of the epithelium and stroma, has no instrument contact with the cornea, takes less surgical time, less postoperative pain, faster wound healing and faster visual recovery than conventional PRK [9].…”
Section: Introductionmentioning
confidence: 99%
“…The shorter epithelial healing time after tPRK observed in our study has been shown in other clinical studies evaluating tPRK treatments performed with other nomograms and other laser systems. Fadlallah et al observed an average period to complete healing of 2.5 days in the tPRK group versus 3.7 days in the conventional PRK group while Naderi et al reported 2.9 days and 3.3 days respectively [11,13]. Although these results were obtained in different studies and therefore cannot be directly compared, it still has to be noted that in our study complete closure of the epithelium after StreamLight TM tPRK was achieved in average after 46 hours, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, patients evaluated their subjective maximum pain intensity level within the rst four days after surgery on a numeric pain rating scale (0-15) which was completed by the patients themselves. Accordingly, pain could be rated as low (1-5), high (6-10) or very high (11)(12)(13)(14)(15). Wound healing was followed during daily slit lamp examinations until day 4.…”
Section: Pre-and Postoperative Assessmentsmentioning
confidence: 99%